Minecraft Redstone handbook - Farwell, Nick; Steer, Don; Burlinson, James; Cordner, Theo; Bolder, Joe; Mojang AB (Firm) (New York, NY : Scholastic Inc., 2015)
Here's everything you need to know to get connected to the electrifying possibilities of redstone. From basic mining and logic circuits to more advanced mechanics, this book will give you step-by-step instructions to get you fully wired to redstone. With builds including redstone traps and arrow launchers, you'll never fear creepers again!"--Back cover.
Redstone essentials. Redstone ore -- Redstone dust -- Redstone torch -- Redstone repeater -- Piston -- Sticky piston -- Power sources -- Slime blocks -- Lighting systems -- Piston doors -- Minecart stations -- Pulse shortener -- Toggle flip-flop -- Clock circuits -- Redstone challenges. Deluxe lighting system -- Automated chicken farm -- Classic Jeb door -- Lava pit trap -- Dual shot cannon -- Supercharged fire arrow launcher -- 3x3 piston door -- Potion lab -- Community creations. 14 floor elevator by Cubehamster -- Color map display by Sethbling -- Super stopwatch by JL2579 & Cubehamster -- Gold rush by CNB -- Zombie siege by FVDisco -- Hints and tips -- Useful links.
"First published 2014."
"Mojang."
Includes bibliographical references.
Keywords: Minecraft (Game) -- Handbooks, manuals, etc. -- Juvenile literature; Video games -- Handbooks, manuals, etc. -- Juvenile literature; Minecraft (Game) -- Handbooks, manuals, etc; Video games -- Handbooks, manuals, etc; Minecraft (Game); Video games; Handbooks and manuals; Juvenile works; Handbooks and manuals